EFEK NEUROPSIKIATRIK PADA PENYALAHGUNAAN PIL ZENITH (CARNOPHEN) OLEH KULI BANGUNAN DI BANJARMASIN - Mustika Muthaharah; Dewi Nurhanifah; Hendera Hendera (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2019)
Carnophen is a muscle relaxant that works centrally, prescribed to relieve muscle spasms and pain. Recent scientific evidence confirms that carisoprodol abuse results in dangerous side effects, such as sudden psychomotor disorders and drug withdrawal resulting in hallucinations, seizures, and deaths. Abuse of this muscle relaxant in Banjarmasin was increased. The circulation is also increasingly widespread and can be bought easily and cheap prices by the public. Whereas the production permit and marketing permit for this drug have been stopped by BPOM since 2009. Weak economic communities with profane labor professions such as laborers and construction workers often consume zenith drugs for reasons not to get tired easily. This study was conducted to identify the neuropsychiatric effects that arise in zenith pill abuse (Carnophen) by construction workers in Banjarmasin. This study uses an observational design with a cross-sectional approach. This research was conducted using accidental sampling technique. Data collection was conducted in May - October 2018 using the Depression Anxiety Stress Scale - 42 questionnaire instrument (DASS 42). Data analysis was carried out with qualitative analysis of Mile's and Huberman. The results showed that from 12 research subjects for 66% stress scale experienced mild stress, 16.6% moderate stress and the remaining 16.6% normal. For anxiety scale, 8.33% experienced mild anxiety, 75% experienced moderate anxiety and 16.6% experienced severe anxiety. For depression scale, 83.3% had moderate depression and 16.6% had severe depression. The results showed that zenith abuse can cause neuropsychiatric effects such as stress, anxiety, and depression.